Determination of maximum possible contribution of porous particles in gas transport properties of their corresponding mixed matrix membranes. (4th December 2020) - Maghami, Saeid; Sadeghi, Morteza; Mehrabani‐Zeinabad, Arjomand; Simiari, Mehdi
Abstract: Due to the partial/total blockage of dispersed porous particles in polymer matrices, porous particles do not change the transport properties of mixed matrix membranes (MMMs) as much as possible. Also, the determination of MMMs' intrinsic gas permeability is very difficult. Hence, a new modeling approach was developed to determine the maximum contribution of porous particles in gas separation properties of MMMs without any need to know the interfacial morphology type. Moreover, the approach allowed determination of the effect of the interfacial layer on gas transport properties of MMMs containing porous particles. The validity of the proposed method was evaluated using literature data in which the intrinsic permeability of the used particles and polymer matrix for the preparation of their MMMs has been measured. Abstract :